Gambaran Pengetahuan dan Penerapan Diet Rendah Garam - Nikmah Rokhmani; Yufitriana Amir; Syeptri Agiani Putri (Jurnal SMART Keperawatan, 2024)
Introduction: Hypertension is a disease that often occurs without complaints with systolic blood pressure equal to or above 140 mmHg and diastolic pressure equal to or above 90 mmHg. Objective: This study aims to describe the knowledge and application of a low salt diet in hypertensive patients in the Rejosari Community Health Center working area. Method: This research method uses descriptive research with a quantitative design and a cross-sectional approach. The sample was 77 respondents using proportional random sampling technique. The research instrument used a questionnaire and 24 hour food recall. Research analysis uses univariate analysis. Results: There were 38 people (49.3%) who had poor knowledge about a low salt diet. A total of 43 people (55.8%) did not comply with the recommended implementation of a low salt diet, namely RG 1 as many as 3 people (3.9%), RG 2 as many as 15 people (19.5%), and RG 3 as many as 25 people. people (32.4%). Conclusion: The majority of knowledge about a low salt diet among hypertensive patients in the Rejosari health center working area is in the poor and sufficient categories and most respondents are not suitable for implementing the recommended low salt diet.